Wywiad, reportaż i korespondencja na łamach wybranych dodatków kulturalnych do prasy codziennej dwudziestolecia międzywojennego - Mikosz, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
The article presents selected press kinds, which appeared before the Second World War in the supplements to the every day newspapers. We can distinguish: interview, reportage and correspondence. The author discusses them for instance sciencc-litcrature appendixes, film appendixes, radio appendixes and illustrated appendixes.